(untitled) (Journal of Hama University, 2024)
The research aimed to reveal the effectiveness of a proposed program for early intervention based on the use of artistic and formative activities in developing visual perception skills for children with hearing disabilities, as the number of the research sample was 14 children from kindergarten children with hearing disabilities. To achieve the objectives of the research and test the validity of its hypotheses, the following tools were used: A proposed program based on employing artistic and formative activities to develop visual perception skills for hearing impaired children. - Illustrated Visual Perception Skills Scale for Hearing Impaired Children, prepared by the researcher. The research reached the following results: 1- The effectiveness of the proposed program based on employing artistic and formative activities in developing visual perception skills for hearing impaired children. 2- There are statistically significant differences between the mean scores of the children of the experimental group in the pre and post measurements on the visual perception skills scale for kindergarten children with hearing disabilities and its sub-dimensions, and the differences are in favor of the post measurement. 3- There are no statistically significant differences between the mean scores of the experimental group children in the post and follow-up measurements on the visual perception skills scale for kindergarten children with hearing disabilities and its sub-dimensions.